Reliability of a field and laboratory test of repeated sprint ability - Oliver, J. L.; Williams, C. A.; Armstrong, N. (Pediatric Exercise Science, 2006)
The purpose of this study was to assess the reliability of a field and a laboratory test of repeated sprint ability (RSA). Twelve adolescent boys (15.3 ± 0.3 years) completed five trials of both a field RSA test (7 × 30 m sprints) and a laboratory RSA test (7 × 5 s sprints) performed on a nonmotorized treadmill. Mean coefficients of variation (CV) calculated across all trials were < 2.7% for field sprint times, and, in the laboratory, < 2.9% for velocity and < 8.4% for power output. Fatigue indices (FI) calculated from data in both environments exhibited mean CVs > 23%. The inconsistency in the FIs resulted from the mathematical procedures used in the FI calculation methods. Based on the reliability scores, it was concluded that results obtained from measured performance variables in the field and laboratory, and not calculated FIs, should be used to report RSA.